1975
DOI: 10.1152/ajplegacy.1975.229.6.1680
|View full text |Cite
|
Sign up to set email alerts
|

Chymodenin, a duodenal peptide: specific stimulation of chymotrypsinogen secretion

Abstract: Chymodenin, a basic porcine duodenal peptide, was administered to anesthetized rabbits intravenously or added to the medium bathing the isolated pancreas. In the 10(-8)M range, chymodenin rapidly increased chymotrypsinogen (ChTg) secretion, did not increase lipase secretion, and modestly enhanced protein secretion (which could be attributed primarily to augmented ChTg secretion). The increased ChTg output was too rapid to be the result of increased rates of protein synthesis and could not be attributed to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Besides, most of the experiments that have demonstrated adaptation of the exocrine pancreas to the diet, have mainly been done in anaesthetized animal (LaBella et al, 1981;Tseng et al, 1982) in perfused organs or in vitro preparations of the gland (Rothman, 1967(Rothman, , 1976Adelson & Rothman, 1975;Palade, 1975;Rothman & Wilking, 1978;Dagorn, 1979) whereas experiments in conscious animals, under nearly physiological conditions, are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, most of the experiments that have demonstrated adaptation of the exocrine pancreas to the diet, have mainly been done in anaesthetized animal (LaBella et al, 1981;Tseng et al, 1982) in perfused organs or in vitro preparations of the gland (Rothman, 1967(Rothman, , 1976Adelson & Rothman, 1975;Palade, 1975;Rothman & Wilking, 1978;Dagorn, 1979) whereas experiments in conscious animals, under nearly physiological conditions, are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Rothman as well as others have shown that secretion of pancreatic enzymes can occur in a non-parallel fashion, so that the nature of the pancreatic juice does not correspond to a homogeneous mixture of all pancreatic enzymes. Selective discharge of certain proteins does occur under particular conditions of stimulated secretion (Adelson and Rothman 1975;Rothman 1976Rothman , 1981Dagorn, 1978;Adelson and Miller 1985;Sommer et al 1985;Rothman et al, 1991;de Dios et al 1999). On the other hand, Anderson, Jena, and colleagues (Anderson 2004;Jena 2004Jena , 2009) have introduced the concept of a discharge mechanism different from the classical exocytotic event (in which the entire granule fuses in one single event with the plasma membrane).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was postulated that this change in composition of secreted en zymes is specific to the diet fed, e.g. that dur ing digestion of a carbohydrate meal, the secretion of amylase is much more pro nounced than that of other enzymes [7,32], An increasing number of studies attempt to confirm or to disprove these findings using in vitro rabbit pancreas [1,26,27,30,31], guinea pig pancreatic lobules [22], anesthe tized or conscious rats [4-7, 9, 11, 17, 32], Even when independent groups used appar ently the same experimental protocol, differ ent results were obtained [9,11,17,26,27,30,31]. Remarkably few experiments have been done in conscious rats [4,5] compared to the numerous in vitro techniques.…”
Section: Discussionmentioning
confidence: 99%
“…It was substituted by an equivalent amount of prccollected juice. Thereafter, the secretion rate was stimulated for at least I h by several different meth ods: (1) h; n = 9); (3) intraduodenal infusion of a amino acid mixture (Aminopaed®; n = 8); (4) intraduodenal infu sion of a lipid mixture (Intralipid®, 10%; n = 8); (5) in traduodenal infusion of 10% sucrose (n = 8). In con trol experiments the basal pancreatic secretion rate was studied under complete recirculation of the juice or under intraduodenal or intravenous infusion of 0.9% NaCl.…”
Section: Animal Experimentsmentioning
confidence: 99%
See 1 more Smart Citation